The Identification of Effective Factors on Intellectual Capital Reporting of the Universities of Iran - Khalili, Yassaman; Fakhari, Hossein; Malekian, Esfandiar; Aghajani, Hassanali (International Journal of Economics and Financial Issues, 2017)
The aim of this research is identifying the effective factors on the intellectual capital reporting in the universities of Iran. In this research, first of all by investigating the research literature and the reports of intellectual capital of universities, 258 indicators were identified. Then they were sent to the experts of the government universities of Iran through questionnaires. From these indicators 49 indicators were selected through Fuzzy Delphi method to be suitable for the intellectual capital reporting on the universities of Iran. These identified indicators were both quantitative and qualitative. As there is not any reporting model of intellectual capital for the universities of Iran, the identification of these factors can be very important for the design of the intellectual capital reporting model suitable for the universities of Iran. Keywords: Intellectual capital Reporting, University, Fuzzy Delphi method JEL Classifications: E22, F43, M41